Latest Innovations in the Treatment of Degenerative Diseases - Sembiring, Lisma Natalia Br; Astuti, Aldiana; Nazaruddin, Muhammad; Muntasir, Muntasir; Hasyim, Dadang Muhammad (Journal of World Future Medicine, Health and Nursing, 2024)
Recent innovations in the treatment of degenerative diseases have become a major focus of efforts to improve the quality of life of patients. With the development of technology and scientific research, there are opportunities to develop more effective and innovative treatment methods. In this study, we aim to explore recent innovations in the treatment of degenerative diseases, the purpose of which is to showcase the latest developments in the field of medicine that can provide new solutions in the management of degenerative diseases. The research method involved a literature review of recent studies in the treatment of degenerative diseases, as well as an analysis of relevant research data. The results showed some promising recent innovations, such as gene therapy, the use of stem cell technology, nanotechnology in drug delivery, and electromagnetic field approaches in medicine. These innovations offer the potential to improve treatment effectiveness and reduce the negative impact of these degenerative diseases. From the results of this study, it can be concluded that recent innovations in the treatment of degenerative diseases offer new hope in the management of these diseases. Technological developments and scientific research provide opportunities for the development of more effective and innovative treatment methods. However, despite significant progress in this field, further research is needed to evaluate the effectiveness, safety and sustainability of these innovations. This conclusion underscores the importance of collaboration between scientists, clinicians and the pharmaceutical industry to continue to drive innovation in an effort to holistically address degenerative diseases.